Detection of nitrite based on fluorescent carbon dots by the hydrothermal method with folic acid - Lin, Haitao; Ding, Liyun; Zhang, Bingyu; Huang, Jun (Royal Society open science, 2018)
A fluorescent carbon dots probe for the detection of aqueous nitrite was fabricated by a one-pot hydrothermal method, and the transmission electron microscope, X-ray diffractometer, UV–Vis absorption spectrometer and fluorescence spectrophotometer were used to study the property of carbon dots. The fluorescent property of carbon dots influenced by the concentration of aqueous nitrite was studied. The interaction between the electron-donating functional groups and the electron-accepting nitrous acid could account for the quenching effect on carbon dots by adding aqueous nitrite. The products of the hydrolysis of aqueous nitrite performed a stronger quenching effect at lower pH. The relationship between the relative fluorescence intensity of carbon dots and the concentration of nitrite was described by the Stern–Volmer equation (I0/I − 1 = 0.046[Q]) with a fine linearity (R2 = 0.99). The carbon dots-based probe provides a convenient method for the detection of nitrite concentration.